A Prevalence Study of Intestinal Parastic Infections in Patient Attend to Elajcentre - Wahaj M Mohammed; Mohammed Ismail Garbi (Journal of Parasite Research, 2019)
Among 500 persons referred to laboratories for performing stool examinations samples (51.43%) were male and (48.57%) were female, all this personshad Abdominal pain and Diarrhea and 39% had a blood in their stool Among these numbers, 298 (59.6%) were positive for parasitic infections 90 (30.2%) Giardia lamblia and 208 (69.8%) Entamoeba histolytica .Also the higher infection rates were recorded in the age 10-19 the infection was (42 % Based on the reliable answers obtained from the interviewed patients or guardians using the pre-formatted questionnaires.The prevalence of intestinal protozoan according to drinking water materials the Plastic and brass have higher infection rate with (50.3%) and (30.2%).
Keywords: Intestinal Parasitic Infections